CONCORDANCE BETWEEN REMISSION DEFINED BY PATIENTS VS PATIENT-REPORTED OUTCOME MEASURES IN INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Kamp, Kendra; Tse, Chung Sang; Hawes, Steven; Oberai, Ridhima; Weaver, Alandra; Singh, Siddharth; Melmed, Gil; Siegel, Corey; van Deen, Welmoed
Abstract: BACKGROUND: Although validated patient-reported outcome measurements (PRO) can categorize patients with inflammatory bowel disease (IBD) into remission or active disease, patients may have different definitions of remission. Patients may assume a new normal with altered bowel habits/abdominal pain after diagnosis or consider themselves to have active disease even though disease activity measures show remission. We aim to examine concordance between patient-defined remission and remission based on PRO-2 (ulcerative colitis; UC) or PRO-3 (Crohn's disease; CD), and associations with demographic and disease-related factors. METHODS: We retrospectively analyzed 3257 de-identified surveys from 2004 unique patients (806 UC; 1198 CD) who consented to participate in the Crohn's and Colitis Foundation's IBD Qorus Learning Health System. Surveys were collected at IBD clinic visits between September 2019 and February 2021. We used logistic regression models with generalized estimating equations to analyze the sensitivity, specificity, concordance, and discordance between patient-defined remission (yes/no) and PRO-defined remission (PRO-2: stool frequency, rectal bleeding; PRO-3: stool frequency, abdominal pain, wellbeing). We also examined steroid-free PRO remission (PRO-defined remission plus absence of steroids). RESULTS: In CD, 63.3% of patients with inactive disease based on PRO-3 considered themselves in remission (adjusted sens=0.62). Discordance was more common among patients with <5 years disease duration (OR 1.6), and those who used prednisone (OR 4.2) or opioids (OR 5.3). Among patients with active disease based on PRO-3, 20.8% considered themselves in remission (adjusted spec=0.79) and discordance was more common with long disease duration (>15 years; OR 2.6) and those who did not use prednisone (OR 3.0) and opioids (OR 5.4). In UC, 77% of patients with inactive disease based on PRO-2 considered themselves in remission (adjusted sens=0.77). Discordance was more common among patients with disease duration of <5 years compared to those >15 years (OR 2.3). Among patients with active disease based on PRO-2, 19.2% considered themselves in remission (adjusted spec=0.79) and discordance was more common in patients who did not use prednisone (OR: 2.2). Age and gender were not associated with discordance. Results were similar with steroid-free PRO defined remission (Table 2). CONCLUSION: Discordance between how patients and PRO measures define remission is common. Patients with shorter disease duration were more likely to report active disease when they were in remission while patients with longer disease duration were more likely to report remission while they still experienced symptoms. 1 in 3 (32%) assessments of disease remission were discordance among patients with CD, and 1 in 4 (22%) in patients with UC.